The options are:
[tex](A)\neg p \land (f \lor h)\\(B)(\neg p \land f) \lor h\\(C)\neg p \land f \land h\\(D)\neg( p \land f) \lor h[/tex]
Answer:
[tex](B)(\neg p \land f) \lor h[/tex]
Explanation:
Given the propositional variables:
The negation of p, [tex]\neg p=$The student is not on academic probation[/tex]
Therefore, the logical expression for the statement:
"The student is not on academic probation and the student got an A on the final " is: [tex]\neg p \land f[/tex]
Therefore, the logical expression for the given statement
"The student is not on academic probation and the student got an A on the final or turned in all the homework."
is: [tex](\neg p \land f) \lor h[/tex]
The correct option is B.